2022
DOI: 10.1186/s13148-022-01343-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA methylation-regulated genes as potential biomarkers for coronary heart disease via machine learning in the Framingham Heart Study

Abstract: Background DNA methylation-regulated genes have been demonstrated as the crucial participants in the occurrence of coronary heart disease (CHD). The machine learning based on DNA methylation-regulated genes has tremendous potential for mining non-invasive predictive biomarkers and exploring underlying new mechanisms of CHD. Results First, the 2085 age-gender-matched individuals in Framingham Heart Study (FHS) were randomly divided into training set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although there are numerous models for predicting incident CHD, 73 to our knowledge, this is the first integrated genetic–epigenetic algorithm for current CHD status. In 2022, Zhang and colleagues 74 described 3 different machine learning models that used genome‐wide methylation and expression information to predict current CHD status in the FHS. The performance metrics of each of the models were similar to the current values, but there was no external validation and no translation of either the methylation or expression assessments into a clinically implementable format.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous models for predicting incident CHD, 73 to our knowledge, this is the first integrated genetic–epigenetic algorithm for current CHD status. In 2022, Zhang and colleagues 74 described 3 different machine learning models that used genome‐wide methylation and expression information to predict current CHD status in the FHS. The performance metrics of each of the models were similar to the current values, but there was no external validation and no translation of either the methylation or expression assessments into a clinically implementable format.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this may be an excellent opportunity for artificial intelligence (AI) to further its role in the derivation and implementation of this testing technology. AI technologies for aggregating and analyzing methylation and genetic data are increasingly commonplace [ 43 , 44 ]. These tools will need to be integrated with tools for parsing clinical laboratory or text data from the electronic medical records in order to create a more complete understanding of the performance and implications of these technologies in the real world [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) traits have been explored via EWAS, such as ischaemic stroke [ 229 ]. In the Framingham Study, biomarkers of CVD were identified through ML by combining DNAm and RNA data in a decision tree, light gradient-boosting machine (LightGBM) [ 230 ]. These were subsequently confirmed in isolated monocytes.…”
Section: Epigenome-wide Association Studies (Ewas)mentioning
confidence: 99%